"The Yellow Wallpaper": How Figurative Languages Fuel a Descent into Madness - Kresnawaty, Novy; Ena, Ouda Teda; Budiraharjo, Markus (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the use of figurative language in Charlotte Perkins Gilman's "The Yellow Wallpaper," focusing on the protagonist's descent into madness as depicted by the author. This study employs a qualitative descriptive methodology, drawing its data from specific sentences from the short story and focusing on some examples of figurative language. The method of analysis utilised is content analysis with a focus on language style. The collected data consists of words and sentences extracted from "The Yellow Wallpaper." This involves conducting a literature review, annotating the text, identifying figurative language techniques, and analysing their effects. Additionally, the study contextualises Gilman's work within its historical and cultural context. This research plan offers a methodical strategy for illuminating this significant aspect of "The Yellow Wallpaper.